Modified high-performance lithium battery diaphragm and preparation method thereof
By applying and modifying the lithium-ion battery separator to the ethylene-vinyl alcohol copolymer, a dual continuous network structure is formed, which solves the problems of poor wettability and poor electrochemical performance of the separator electrolyte, and significantly improves the electrochemical performance of the battery and stability.
Patent Information
- Application Number
- CN202411650124.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
AI Technical Summary
The commercial separators of existing lithium-ion batteries have poor wettability to the electrolyte and have poor electrochemical performance, which cannot meet the performance requirements of higher energy density and fast charging and discharge.
The commercial polyolefin lithium-ion battery separator is coated and modified by using ethylene-vinyl alcohol copolymer (EVOH). The coating layer with a dual continuous network structure is formed through immersion-precipitation phase separation technology, which improves the electrolyte absorption rate of the separator and Conductive efficiency of lithium ions.
It significantly improves the electrochemical performance of the separator, improves the electrolyte absorption rate and ionic conductivity, enhances the charging and discharging efficiency and stability of the battery, and extends the cycle life of the battery.
Smart Images

Figure CN119481565A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery separators, and in particular to a modified high-performance lithium battery separator and a preparation method thereof. Background Art
[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.
[0003] Lithium-ion batteries have gradually become the most widely used energy storage system in the world due to their high energy density, low self-discharge rate, and no memory effect. As one of the components in lithium-ion batteries, the separator does not participate in the electrochemical reaction, but it plays a vital role. It not only isolates the positive and negative electrodes from contact, but also provides a necessary channel for the transport of lithium ions.
[0004] Since the birth of the first commercial lithium-ion battery, polyolefin (polyethylene or polypropylene) microporous membranes have occupied half of the lithium-ion battery commercial separator market, thanks to its low price, good chemical and electrochemical stability, excellent mechanical strength, etc. However, due to its inherent low polarity, it is difficult for the electrolyte to completely infiltrate the separator, so there are pores inside the separator that are not completely filled with electrolyte, which will cause lithium ions to encounter greater resistance when passing through the separator, limiting the performance of the separator in terms of electrochemical performance. Therefore, simple polyolefin separators have become increasingly unable to meet people's increasing demand for higher energy density and fast charging and discharging performance. Modification of polyolefin separators has become one of the necessary means to prepare modified high-performance lithium-ion battery separators.
[0005] Many methods have been developed to modify the diaphragm to increase its surface wettability, such as surface plasma treatment, surface chemical grafting, etc. However, due to the difficulty of implementation and cost considerations, the most widely used is surface coating technology. Inorganic nanoparticles are often used for surface coating of polyolefin diaphragms. After being mixed with adhesives and solvents to form a coating liquid in a certain proportion, they are evenly coated on the surface of the diaphragm, and the wettability of the diaphragm is greatly improved. However, there are also some potential limitations in the use of inorganic nanoparticles during coating. First, these particles are easy to fall off from the surface of the diaphragm during the cycle of the battery, which may block the pores of the diaphragm, hinder the flow of electrolyte, and even cause partial failure of the battery. In addition, the pores of the modified layer are usually formed by random accumulation of inorganic nanoparticles. Such a pore structure may not provide the ideal channel required for efficient lithium ion transport, thereby affecting ionic conductivity and overall battery performance. More importantly, the inorganic nanoparticle layer may cause poor contact between the diaphragm and the electrode, increase the interface impedance, and limit the charging and discharging efficiency and stability of the battery. The above factors will have certain adverse effects on the overall performance of the battery, and urgently need to be optimized through modification methods.
[0006] In order to overcome the limitations of inorganic nanoparticles in coating modification, polymer-based modification methods have gradually become a research hotspot. Polymer materials have good flexibility and adhesion, and can form a uniform and stable modified layer on the surface of the diaphragm, effectively reducing the problems of particle shedding and pore clogging. In addition, the controllability of polymer materials enables them to optimize the pore structure and improve the transport efficiency of lithium ions in the diaphragm. Ethylene-vinyl alcohol copolymer (EVOH) is an ideal choice for modified diaphragms due to its unique hydrophilicity, good mechanical properties and chemical stability. After coating the diaphragm, EVOH can significantly improve the electrolyte wettability and thermal stability of the diaphragm, while promoting the conduction of lithium ions through its porous structure, further improving the electrochemical performance of the battery. This polymer modification strategy provides new ideas and methods for the development of high-performance lithium-ion battery diaphragms. Summary of the invention
[0007] The purpose of the present invention is to provide a modified high-performance lithium battery separator and a preparation method thereof in view of the shortcomings of the existing commercial lithium-ion battery separators, which have poor wettability to electrolytes and poor electrochemical performance. The existing commercial polyolefin lithium-ion battery separators with poor electrolyte affinity are coated and modified by using ethylene-vinyl alcohol polymers, and the electrochemical performance of the separators is effectively improved without losing the mechanical properties and thermal stability of the separators. The vinyl alcohol units in the ethylene-vinyl alcohol copolymers carry abundant side hydroxyl groups, which can bring excellent electrolyte affinity to the separators. A coating layer with a double continuous network structure is formed by simple immersion-precipitation phase separation. This rich in a large amount of The interconnected pore structure helps to increase the overall porosity of the diaphragm, provide more space for storing electrolyte, and increase the electrolyte absorption rate of the diaphragm, thereby improving the electrochemical performance of the diaphragm; in addition, the coating layer contains a large number of hydroxyl groups with unshared electron pairs as lithium ion action sites, which can accelerate the dissociation of lithium ions, promote the passage of lithium ions through the diaphragm while inhibiting the transmission of anions; at the same time, this soft coating layer also enables the diaphragm and electrode components to achieve a better fit in the actual use environment of the battery, which is more conducive to the transmission of lithium ions; in summary, the use of this modified high-performance ion battery diaphragm will effectively improve the electrochemical performance of lithium-ion batteries.
[0008] The technical solution of the present invention is as follows:
[0009] A modified high-performance lithium battery separator comprises: a commercial separator and a modified layer attached to one side of the commercial separator; the modified layer is obtained by immersion-precipitation phase separation of an ethylene-vinyl alcohol polymer (EVOH) solution.
[0010] Furthermore, the commercial separator is a polyethylene separator or a polypropylene separator with a thickness of 12-25 μm.
[0011] Furthermore, the thickness of the modified layer is 1-4 μm.
[0012] The present invention also proposes a method for preparing a modified high-performance lithium battery separator, comprising:
[0013] Step S1: preparing a coating liquid; weighing ethylene-vinyl alcohol copolymer, adding it into a solvent according to a certain solid content ratio, heating to a certain temperature, and stirring for a certain time until a completely transparent coating liquid is obtained;
[0014] Step S2: dropping the coating liquid onto the commercial separator, and using a coating tool to evenly spread the coating liquid on the commercial separator;
[0015] Step S3: The coated membrane is transferred to a coagulation bath, and after standing for a period of time, the membrane is taken out and dried after the immersion-precipitation phases are completely separated.
[0016] Furthermore, the solid content of the ethylene-vinyl alcohol copolymer solution is 5-15%.
[0017] Furthermore, the solvent is nitrogen methyl pyrrolidone (NMP) or dimethyl sulfoxide (DMSO).
[0018] Furthermore, in step S1, the heating temperature is 90-110° C., the stirring rate is 400-500 rpm, and the stirring time is 3-6 hours.
[0019] Furthermore, the coating tool in step S2 includes: a scraper, a color spreading rod or a wire rod, and the thickness is 10-20 μm.
[0020] Furthermore, the coagulation bath in step S3 is water or ethanol, and the temperature is 25° C.; the standing time required for immersion-precipitation phase separation is 30-60 minutes.
[0021] Furthermore, the drying conditions in step S3 are: drying in a vacuum oven at 50-80° C. for 10-14 hours.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1. The present invention uses low-priced and easily available ethylene-vinyl alcohol copolymer (EVOH) as a modified material, and the coating effect can be achieved without the use of additional adhesives. This material has moderate viscosity and can be firmly bonded to the base film, reducing the dependence on complex bonding systems. At the same time, the process adopts a simple immersion-precipitation phase separation technology, and the formation of a double continuous network microporous structure is achieved through the interaction between the solvent and the non-solvent. This structure can effectively avoid clogging of the membrane pores while maintaining the adhesion of the coating. In addition, compared with other complex processes with multiple steps and multiple solvents, this method has fewer steps and is easy to operate. It not only simplifies the coating process, but also reduces production costs and solvent consumption. It can better meet the requirements of industrial production, has good economy and feasibility, and is convenient for large-scale promotion and application.
[0024] 2. The modified diaphragm of the present invention exhibits significantly improved electrolyte affinity. The abundant hydroxyl groups in EVOH have good compatibility with electrolyte molecules, and the wettability of the modified diaphragm in the electrolyte is greatly improved. Benefiting from the improvement in electrolyte affinity and the increase in the porosity of the diaphragm, the electrolyte absorption rate of the EVOH-coated diaphragm is about doubled compared with the traditional polyolefin diaphragm, providing more space for the storage of the electrolyte. This bicontinuous microporous structure provides a stable channel for the penetration and retention of the electrolyte, making it easier for the electrolyte to be evenly distributed in the diaphragm, ensuring smooth ion transmission in the battery. The improved electrolyte absorption rate not only enhances the ionic conductivity of the diaphragm, but also lays the foundation for the stability of high-rate charge and discharge, thereby better exerting the overall electrochemical performance of the battery during use.
[0025] 3. The EVOH coating layer of the modified diaphragm of the present invention carries a large number of hydroxyl groups, and the hydroxyl groups carry unshared electron pairs, which can serve as dissociation sites for lithium ions, helping to increase the concentration of free lithium ions and improve the ion transmission rate. This characteristic enables the diaphragm to efficiently transmit lithium ions. At the same time, under the action of hydroxyl groups, the transmission of negatively charged anions is effectively inhibited, thereby reducing the competition effect of ion channels. By preferentially conducting lithium ions, this coating structure significantly improves the ionic conductivity and lithium ion migration number of the battery, allowing the battery to exhibit better stability and output performance under high current conditions. In addition, this characteristic extends the cycle life of the battery and maintains a high capacity retention rate under high-rate charge and discharge, fundamentally improving the service life and safety of lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 It is a flow chart of a method for preparing a modified high-performance modified lithium battery separator;
[0027] Figure 2The scanning electron microscope photos of the surface morphology before and after the membrane coating, wherein a is the surface morphology of the PE base membrane in Comparative Example 1, and b is the surface morphology of the modified PE membrane prepared in Example 2;
[0028] Figure 3 The water contact angle and electrolyte contact angle test photos of the diaphragm, wherein a and b are the water contact angles of Comparative Example 1 and Example 2, respectively, and c and d are the electrolyte contact angles of Comparative Example 1 and Example 2, respectively;
[0029] Figure 4 The AC impedance spectra obtained by measuring the stainless steel sheet 2032 button cell using the stainless steel sheet assembled with the diaphragms of Example 2 and Comparative Example 1;
[0030] Figure 5 The discharge capacity diagram is a graph of a full battery assembled using Example 2 and Comparative Example 1 and cycled for 200 cycles at 1C current. DETAILED DESCRIPTION
[0031] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0032] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0033] Example 1
[0034] A method for preparing a modified high-performance modified lithium-ion battery separator comprises the following steps:
[0035] Step S1: preparing a coating liquid; weighing 5 g of ethylene-vinyl alcohol copolymer and 95 g of NMP solution, placing them into a round-bottom flask, and stirring them in an oil bath at 100° C. at 500 rpm for 6 hours to obtain a transparent coating liquid;
[0036] Step S2: use a rubber-tipped dropper to absorb an appropriate amount of coating liquid, drop it onto a commercial PE diaphragm with a thickness of 12 μm, and use a 20 μm scraper to evenly coat the coating liquid on the surface of the diaphragm;
[0037] Step S3: The coated diaphragm is quickly transferred to deionized water, ensuring that the water temperature is constant at 25°C. It is taken out after 30 minutes, and the diaphragm after complete immersion-precipitation phase separation is placed in a vacuum oven set at 80°C for drying. After 12 hours, a modified high-performance lithium-ion battery diaphragm is obtained.
[0038] Example 2
[0039] A method for preparing a modified high-performance modified lithium-ion battery separator comprises the following steps:
[0040] Step S1: preparing a coating liquid; weighing 10 g of ethylene-vinyl alcohol copolymer and 90 g of DMSO, placing them into a round-bottom flask, and stirring them in an oil bath at 110° C. at a speed of 600 rpm for 4 hours to obtain a transparent coating liquid;
[0041] Step S2: use a rubber-tipped dropper to absorb an appropriate amount of coating liquid, drop it onto a commercial PE diaphragm with a thickness of 12 μm, and use a 10 μm scraper to evenly coat the coating liquid on the surface of the diaphragm;
[0042] Step S3: The coated diaphragm is quickly transferred to deionized water, ensuring that the water temperature is constant at 25°C. It is taken out after 1 hour, and the diaphragm after complete immersion-precipitation phase separation is placed in a vacuum oven set at 70°C for drying. After 14 hours, a modified high-performance lithium-ion battery diaphragm is obtained.
[0043] Example 3
[0044] A method for preparing a modified high-performance modified lithium-ion battery separator comprises the following steps:
[0045] Step S1: preparing a coating liquid; weighing 15 g of ethylene-vinyl alcohol copolymer and 85 g of NMP, placing them into a round-bottom flask, and stirring them in an oil bath at 110° C. at a speed of 800 rpm for 6 hours to obtain a transparent coating liquid;
[0046] Step S2: use a rubber-tipped dropper to absorb an appropriate amount of coating liquid, drop it onto a commercial PP diaphragm with a thickness of 25 μm, and use a 10 μm scraper to evenly coat the coating liquid on the surface of the diaphragm;
[0047] Step S3: The coated diaphragm is quickly transferred to deionized water, ensuring that the water temperature is constant at 25°C. It is taken out after 1 hour, and the diaphragm after complete immersion-precipitation phase separation is placed in a vacuum oven set at 80°C for drying. After 14 hours, a modified high-performance lithium-ion battery diaphragm is obtained.
[0048] Comparative Example 1
[0049] 12 μm thick commercial PE separator.
[0050] Comparative Example 2
[0051] 25 μm thick commercial PP separator.
[0052] The basic performance parameters of the modified high-performance lithium-ion battery separators prepared in Examples 1-3 and Comparative Examples 1 and 2 are shown in Table 1 below.
[0053] Table 1 Test results
[0054] Thickness(μm) Gurley value (S) Porosity (%) Liquid absorption rate (%) Example 1 14 277 51 218 Example 2 14 282 50 225 Example 3 28 299 47 212 Comparative Example 1 12 230 45 109 Comparative Example 2 25 247 42 102
[0055] As can be seen from Table 1, after coating, the thickness of the diaphragm increases. This increased thickness will increase the resistance of the gas passing through the diaphragm, so the Gree values of Examples 1, 2, and 3 are slightly increased compared to Comparative Examples 1 and 2. The porosity of Examples 1 and 2 increases from the original porosity of 45% of the PE diaphragm to 51% and 50%, and the porosity of Example 3 increases from 42% of the original PP diaphragm to 47%. This is because the bicontinuous microporous network structure formed in the coating layer has an extremely high porosity. The higher porosity of the diaphragm means that more space can be provided for electrolyte storage, which will help improve the overall electrochemical performance of the battery. The electrolyte absorption rates of Examples 1, 2, and 3 are much greater than those of PE and PP base films, almost more than twice that of the base films, which comes from the increased porosity of the modified diaphragm and its excellent wettability to the electrolyte.
[0056] Figure 2 The scanning electron microscope photos of the surface morphology before and after the membrane coating, wherein a is the surface morphology of the PE base membrane in Comparative Example 1, and b is the surface morphology of the modified PE membrane prepared in Example 2. It can be seen that after immersion precipitation phase separation, the ethylene-vinyl alcohol polymer coating layer forms a network-interlaced bicontinuous structure on the surface of the base membrane.
[0057] Figure 3 The figures are test photos of the water contact angle and electrolyte contact angle of the diaphragm, wherein a and b are the water contact angles of Comparative Example 1 and Example 2, respectively, and c and d are the electrolyte contact angles of Comparative Example 1 and Example 2, respectively. The surface of the polyolefin diaphragm, which originally has poor polarity, shows poor affinity to water, with a water contact angle of 101.6° and a contact angle with the electrolyte of 40°. The water contact angle of the diaphragm modified in Example 2 is greatly reduced to only 30.9°, and its wettability to the electrolyte is so strong that the contact angle is almost 0°. It can be seen that after modification by coating with ethylene-vinyl alcohol copolymer, the surface wetting properties of the diaphragm are improved, and the surface polarity is increased, which is beneficial to the electrochemical performance of the diaphragm in the battery.
[0058] Figure 4The AC impedance spectrum is measured for a stainless steel sheet 2032 button cell assembled with the diaphragms of Example 2 and Comparative Example 1, wherein the coordinates of the intersection of the extended line of the curve and the horizontal axis represent the bulk impedance of the diaphragm. It can be seen that the bulk impedance of the diaphragm after coating is reduced from 1.4Ω of the PE diaphragm to 1.1Ω. Further calculation results of the ionic conductivity show that the ionic conductivity of the battery equipped with the diaphragm of Example 2 is 0.65mS / cm, while the ionic conductivity of the battery equipped with the diaphragm of Comparative Example 1 is only 0.43mS / cm. The modified high-performance lithium-ion battery after coating has excellent electrolyte wettability, and the abundant lithium ion action sites provided by the hydroxyl groups effectively promote lithium ion transmission.
[0059] Figure 5 In order to use lithium cobalt oxide as the positive electrode and graphite as the negative electrode, full batteries using Example 2 and Comparative Example 1 as separators were assembled respectively, and the cycle stability performance of the two batteries was tested at a charge and discharge rate of 1C. During the cycle, the capacity of the battery equipped with the separator of Example 2 decreased more slowly, and the capacity retention rate was also higher. After 200 cycles, the capacity retention rate of the battery equipped with Example 2 was 90%, while the capacity retention rate of the battery equipped with the separator of Comparative Example 1 was 80%. The better compatibility between the modified separator and the electrode and the excellent wettability of the electrolyte are conducive to the interfacial transmission of lithium ions and improve the discharge capacity of the battery.
[0060] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.
[0061] This background section is provided to generally present the context of the invention, and the work of the presently named inventors, the work to the extent described in this background section, and aspects of this section that did not constitute prior art at the time of application are neither explicitly nor implicitly admitted to be prior art to the present invention.
Claims
1. A modified high-performance lithium battery separator, characterized in that: include: A commercial separator and a modified layer attached to one side of the commercial separator; The modified layer is obtained from an ethylene-vinyl alcohol polymer solution through immersion-precipitation phase separation.
2. A modified high-performance lithium battery separator according to claim 1, characterized in that: The commercial separator is a polyethylene separator or a polypropylene separator with a thickness of 12-25 μm.
3. A modified high-performance lithium battery separator according to claim 1, characterized in that: The thickness of the modified layer is 1-4 μm.
4. A method for preparing a modified high-performance lithium battery separator, characterized in that: include: Step S1: preparing a coating liquid; weighing ethylene-vinyl alcohol copolymer, adding it into a solvent according to a certain solid content ratio, heating to a certain temperature, and stirring for a certain time until a completely transparent coating liquid is obtained; Step S2: dropping the coating liquid onto the commercial separator, and using a coating tool to evenly spread the coating liquid on the commercial separator; Step S3: The coated membrane is transferred to a coagulation bath, and after standing for a period of time, the membrane is taken out and dried after the immersion-precipitation phases are completely separated.
5. The method for preparing a modified high-performance lithium battery separator according to claim 4, characterized in that: The solid content of the ethylene-vinyl alcohol copolymer solution is 5-15%.
6. The method for preparing a modified high-performance lithium battery separator according to claim 4, characterized in that: The solvent is nitrogen methyl pyrrolidone or dimethyl sulfoxide.
7. The method for preparing a modified high-performance lithium battery separator according to claim 4, characterized in that: The heating temperature in step S1 is 90-110° C., the stirring rate is 400-500 rpm, and the stirring time is 3-6 hours.
8. The method for preparing a modified high-performance lithium battery separator according to claim 4, characterized in that: The coating tool in step S2 includes: a scraper, a color spreading rod or a wire rod, and has a thickness of 10-20 μm.
9. The method for preparing a modified high-performance lithium battery separator according to claim 4, characterized in that: The coagulation bath in step S3 is water or ethanol at a temperature of 25° C.; the standing time required for immersion-precipitation phase separation is 30-60 minutes.
10. The method for preparing a modified high-performance lithium battery separator according to claim 4, characterized in that: The drying conditions in step S3 are: drying in a vacuum oven at 50-80° C. for 10-14 hours.
Citation Information
Patent Citations
Diaphragm and preparation method thereof
CN118251267A
Separator for nonaqueous electrolyte battery
JP2021044153A